The Effect of ICA and Non-negative Matrix Factorization Analysis for EMG Signals Recorded From Multi-Channel EMG Sensors - Kim, Yeongdae; Stapornchaisit, Sorawit; Miyakoshi, Makoto; Yoshimura, Natsue; Koike, Yasuharu (Frontiers in Neuroscience, 2020)
Surface electromyography (EMG) measurements are affected by various noises such as power source and movement artifacts and adjacent muscle activities. Hardware solutions have been found that use multi-channel EMG signal to attenuate noise signals related to sensor positions. However, studies addressing the overcoming of crosstalk from EMG and the division of overlaid superficial and deep muscles are scarce. In this study, two signal decompositions, independent component analysis and non negative matrix factorization were used to create a low-dimensional input signal that divides noise, surface muscles, and deep muscles and utilizes them for movement classification. In the case of index finger movement, it was confirmed that the proposed decomposition method improved the performance with the least input dimensions. These results suggest a new method to analyze more dexterous movements of the hand by separating superficial and deep muscles in the future using multi-channel EMG signals.